2021
DOI: 10.33736/ijbs.3250.2020
|View full text |Cite
|
Sign up to set email alerts
|

Signalling Effect of Auditor Reputation and Lock-Up Period on Over-Subscription Ratio: Evidence from Malaysian Fixed-Price IPOs

Abstract: This study investigates the signalling effect of auditor reputation and lock-up period on the subscription demand of investors in the Malaysian IPO market that uses the fixed-price method in pricing IPOs. The study sample covers 420 IPOs listedon Bursa Malaysia from January 2000 to December 2015. The present study employsOrdinary Least Square(OLS)andQuantile Regression(QR)methodsin investigating the signalling effect on over-subscription ratio (OSR). The results indicate that auditor reputation has a negative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 51 publications
(97 reference statements)
0
3
0
Order By: Relevance
“…This study compares consistency in empirical results with the studies of both developed and emerging markets. The third rationale is that existing studies focus upon trading volume changes, short-run performance around lockup expiry, long-run post-IPO performance, IPO prestige signals, and oversubscription [30][31][32][33][34][35][36][37][38]. Studies on long-term corporate perspectives in a public corporation's perpetual Second, IPO characteristics of firms listed on Bursa Malaysia are somewhat a mix of emerging and developed countries' IPO characteristics in terms of market segregation, lock up expiry, share moratoriums (from mandatory and fixed to staggered), listing requirements, and delisting regulations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study compares consistency in empirical results with the studies of both developed and emerging markets. The third rationale is that existing studies focus upon trading volume changes, short-run performance around lockup expiry, long-run post-IPO performance, IPO prestige signals, and oversubscription [30][31][32][33][34][35][36][37][38]. Studies on long-term corporate perspectives in a public corporation's perpetual Second, IPO characteristics of firms listed on Bursa Malaysia are somewhat a mix of emerging and developed countries' IPO characteristics in terms of market segregation, lock up expiry, share moratoriums (from mandatory and fixed to staggered), listing requirements, and delisting regulations.…”
Section: Introductionmentioning
confidence: 99%
“…This study compares consistency in empirical results with the studies of both developed and emerging markets. The third rationale is that existing studies focus upon trading volume changes, short-run performance around lock-up expiry, long-run post-IPO performance, IPO prestige signals, and oversubscription [30][31][32][33][34][35][36][37][38]. Studies on long-term corporate perspectives in a public corporation's perpetual and sustainable survivorship are limited to only descriptive statistics in Malaysia.…”
Section: Introductionmentioning
confidence: 99%
“…Tajuddin et al (2018) found that Shariah IPOs experienced lower oversubscription rates than non-Shariah IPOs. Furthermore, the findings of Albada et al (2019Albada et al ( , 2020 showed that IPOs certified by reputable underwriters and auditors experienced low oversubscription rates among the fixed-price IPOs in Malaysia. Overall, the current study puts forward the notion that other pre-IPO information from IPO prospectuses affects the oversubscription rates, and this topic was not discussed in prior studies.…”
Section: Introductionmentioning
confidence: 99%